A summary of the current circumstances of migraineurs in China: a review of the GBD2019 database - Ying, Changchang; Yu, Qijun; Zhai, Qingling; Pan, Yonghui (Frontiers in Human Neuroscience, 2025)
Migraine is a common, chronic and recurrent neurovascular disorder ranked by the WHO as one of the 20 most disabling conditions worldwide. Frequent and severe headaches can significantly impair patients’ quality of life, learning capacity, and physical and mental health. On the basis of the Global Burden of Disease (GBD) 2019 database, this article reviews the incidence, disability and treatment of migraine in China in recent years. This study aims to analyze the current status of migraine patients in China and to inform future research on its epidemiology, prevention, and treatment.